2019
DOI: 10.3390/ani9090630
|View full text |Cite
|
Sign up to set email alerts
|

Are Horses (Equus caballus) Sensitive to Human Emotional Cues?

Abstract: Simple SummaryIt is important for social animals to be sensitive to others’ emotional cues, because they can process and react to valuable social and environmental information more efficiently if they can understand others’ emotional states. Such sensitivity also seems to be adaptive in animal communication with both conspecific and heterospecific individuals, particularly for dogs and horses, because these animals have been cooperating with humans since the advent of domestication. Previous studies have demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…This adds to the literature showing their sensitivity to human attentive states [24][25][26][27], pointing gestures [28,29], or auditory cues [30]. A recent line of research also showed horses' abilities to discriminate between human emotional facial and vocal expressions [35,38] and to adjust behavior such as looking time and gaze following according to human facial emotional expressions (happy, neutral, disgust) [54]. This might be explained by the observation that unridden horses react to humans more similarly as they do to conspecifics rather than to predators [55] and, thus, seem to consider humans' communicative cues, especially during the evaluation of an ambiguous situation.…”
Section: Discussionmentioning
confidence: 51%
“…This adds to the literature showing their sensitivity to human attentive states [24][25][26][27], pointing gestures [28,29], or auditory cues [30]. A recent line of research also showed horses' abilities to discriminate between human emotional facial and vocal expressions [35,38] and to adjust behavior such as looking time and gaze following according to human facial emotional expressions (happy, neutral, disgust) [54]. This might be explained by the observation that unridden horses react to humans more similarly as they do to conspecifics rather than to predators [55] and, thus, seem to consider humans' communicative cues, especially during the evaluation of an ambiguous situation.…”
Section: Discussionmentioning
confidence: 51%
“…They can communicate emotions both vocally [30] and visually (by body posture and facial features; e.g., Lansade et al [31]). Horses can also discriminate emotions both intra- and interspecifically: they react differently when facing pictures of positive or negative facial expressions of both humans [26,32,33] and conspecifics [34] and when hearing positive or negative nonverbal vocalizations from humans [35] and conspecifics [30]. A recent study from Nakamura et al [36] suggested that horses could recognize human emotions cross-modally in a violation of expectation paradigm (i.e., comparing their behavior when facing an expected and unexpected scene).…”
Section: Introductionmentioning
confidence: 99%
“…As long as animals are present in people’s lives, they offer long-term, additional support for confronting life’s difficulties [ 82 ]. Regarding this issue of support, studies have shown that pets are sensitive not only to the emotional signals of human beings but also of their peers [ 83 ]. Additionally, they seem to represent points of cohesion within families [ 66 ].…”
Section: Discussionmentioning
confidence: 99%